2020
DOI: 10.3389/fmars.2020.571878
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Monitoring an Indo-Pacific Grouper Spawning Aggregation: Benefits of Protection and Importance of Survey Design

Abstract: Groupers (Family Epinephelidae) are valuable and vulnerable reef-associated fishes. Medium to large-sized Indo-Pacific genera, such as Epinephelus and Plectropomus, are important in local/international trade, and are particularly susceptible to overfishing due to their economic value, longevity, late maturation and, for some species, aggregationspawning. Three species, Plectropomus areolatus, Epinephelus polyphekadion, Epinephelus fuscoguttatus, are threatened (IUCN Red List) and, when exploited on their aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Regarding the ecological dimension, it is observed that the CPUE trend, stock status, and changes in the size of the fish caught promote ecological sustainability. A combination of a closed fishing season and a closed area, especially in fish spawning aggregation sites, is recommended to complement conventional fishery management measures [3], [48], mainly to protect juveniles.…”
Section: Strategy For Increasing Effectivenessmentioning
confidence: 99%
“…Regarding the ecological dimension, it is observed that the CPUE trend, stock status, and changes in the size of the fish caught promote ecological sustainability. A combination of a closed fishing season and a closed area, especially in fish spawning aggregation sites, is recommended to complement conventional fishery management measures [3], [48], mainly to protect juveniles.…”
Section: Strategy For Increasing Effectivenessmentioning
confidence: 99%
“…While spawning was not observed for the other species, which we presume spawn at night (e.g. Sadovy de Mitcheson et al, 2020), the definition of spawning aggregations proposed by Domeier and Colin (1997) was fulfilled. For all species other than C. striatus , we sampled aggregations on at least two different days, and for some species at multiple aggregation sites around Palau (Table S1).…”
Section: Methodsmentioning
confidence: 77%
“…While spawning was not observed for the other species, which we presume spawn at night (e.g. Sadovy de Mitcheson et al, 2020), the definition of spawning aggregations proposed by Domeier and Colin (1997) was fulfilled.…”
Section: Size Compositions Of Spawning Aggregationsmentioning
confidence: 81%
See 1 more Smart Citation
“…The species most sensitive to the risk of extinction by fishing are those with large‐sized, slow‐growing and late‐maturing individuals (Denney et al ., 2002; Sadovy, 2001; Tsoukali et al ., 2016). These species are highly valued in the market (due to the quality of the meat) and usually have limited geographical range and sporadic recruitment, such as many grouper species (Chiappone et al ., 2000; Sadovy, 1994; Sadovy, 2001; Sadovy De Mitcheson et al ., 2020; Sáenz‐Arroyo et al ., 2005).…”
Section: Introductionmentioning
confidence: 99%